The evolution of international classification criteria for Sjogren’s syndrome - J. I. Khvan; A. V. Torgashina (Научно-практическая ревматология)
This article presents review of literature of the history of international classification criteria of American College of Rheumatology/European Alliance of Associations for Rheumatology (ACR/EULAR) 2016, considers the features of validation and development of preliminary European criteria 1993, criteria of American European Consensus Group (AECG) 2002 and ACR 2012 criteria.